Misja dyplomatyczna księcia Henryka X Rumpolda w czasie wojny duńsko-holsztyńskiej w latach 1422-1423 = Diplomatic mission of duke Henry X Rumpold in the danish-holstein war 1422-1423 - Karp, Paweł (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Duchy of Schleswig, which till 1326 stayed in possession of Holstein counts, played a significant role in Danish politics in the years of the reign of Queen Margaret and her son Eric. The Queen resigned temporarily from the long-conducted battle of the duchy since at that time she realised the plan of joining the three Scandinavian countries- Denmark, Norway and Sweden. She granted this land to the count of Holstein Gerhard VI to hold in fee. Margaret and Eric returned to their plan of regaining Schleswig when unexpectedly the count died on a battlefield in 1404.
Keywords: Księstwo Głogowskie - 14-15 w.; Henryk X Rumpold (książę głogowski; ok. 1390-1423); historia - 14-15 w.; dyplomacja - historia